RISK ANALYSIS IN COCOA BUSINESS OF THE SARI BUMI PROCESSING UNIT (UPH) IN GUMBRIH VILLAGE, PEKUTATAN DISTRICT, JEMBRANA REGENCY - Ni Luh Prima Kemala Dewi; Putu Gita Nanda Savitri (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2026)
This research was aimed to: identify the risks that occur using each stage of the activity, analyze the risk ranking using the FMEA method, and develop a mitigation plan to minimize the Risk Events that occur in UPH Sari Bumi. UPH Sari Bumi is a Cocoa Product Processing Unit fostered by the Bali Province Agriculture and Food Security Office. UPH Sari Bumi processes fermented dry beans from farmers within UPH members and farmers outside UPH Sari Bumi. Data for this research were collected through interviews, brainstorming, and documentation from October 2023 to January 2024, involving primary and secondary sources. Results reveal 16 risk events across planning, procurement, production, delivery, and sales return stages, with Risk Priority Numbers (RPN) ranging from 7 (broadly acceptable) to 624 (intolerable). Key risks include insufficient harvest (RPN 624), worker negligence (RPN 531), and competition (RPN 392), driven by factors such as limited raw material supply, poor fermentation quality, and lack of legal permits (SIUP). Proposed mitigations include diversifying supply sources, implementing worker training and incentives, securing supplier contracts, and obtaining legal documentation (NIB) to enhance financing and export capabilities.